2022
DOI: 10.3390/catal13010002
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Carbon-Based Materials: A Review of Synthesis, Modification, and Applications

Abstract: Mesoporous carbon materials have attracted both academic and industrial interests because of their outstanding physical and chemical properties, such as high surface area, large pore-volume, good thermostability, improved mass transport, and diffusion. Mesoporous carbon materials with various pore sizes and pore structures can be synthesized via different methods. Their unique properties have made them a suitable choice for various applications, such as energy-storage batteries, supercapacitors, biosensors, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 152 publications
1
10
0
Order By: Relevance
“…Porous carbon-based NMs are superior catalyst beds for heterogeneous catalysis because of their high surface areas, large pore volumes, and controllable pore sizes [159,160]. Porous carbon nanostructures loaded with various metal NPs can catalyze multiple industrially important organic transformations.…”
Section: Porous Carbon-based Nanocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous carbon-based NMs are superior catalyst beds for heterogeneous catalysis because of their high surface areas, large pore volumes, and controllable pore sizes [159,160]. Porous carbon nanostructures loaded with various metal NPs can catalyze multiple industrially important organic transformations.…”
Section: Porous Carbon-based Nanocatalystmentioning
confidence: 99%
“…Recently, Zhang et al reported a novel Ni-embedded porous carbon catalyst, synthesized via hydrothermal synthesis, for the catalytic cracking of biomass tar [161]. Moreover, Gogoi et al described the ability of Cu and Co nanoparticle-decorated porous carbon materials to reduce nitroaromatics to aniline derivatives using NaBH4 [160]. The high efficiency of the catalyst, as well as its reusability, eco-friendliness, easy separation using a strong magnet, and the ability to provide an environmentally friendly reaction pathway were also demonstrated.…”
Section: Porous Carbon-based Nanocatalystmentioning
confidence: 99%
“…Moreover, carbon black (CB) possesses excellent conductivity and cost-effectiveness and can be uniformly dispersed. Compared to other carbon materials, CB exhibits higher stability and good resistance to interference from O 2 , CO 2 , and light. Mesoporous CB (MCB) is characterized by its mesoporous structure (average pore size = 6.4 nm), high specific surface area (>200 m 2 /g), and good conductivity. , Although graphitized MCB (GMCB) exhibits excellent conductivity, untreated MCB possesses a higher surface area and better conductivity. , This may result in a larger double-layer capacitance of the solid-state contact layer, thereby enhancing the stability of the sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we applied the CV-SAXS technique to a commercially available Pt catalyst supported on solid carbon and a mesoporous carbon sample with mesopores whose size was comparable to that of Pt catalysts. Mesoporous carbon has attracted attention as support for catalysts, due to its superior properties as compared with conventional solid carbon, such as increased surface-to-volume ratio [20]. Therefore, it is anticipated that the demands for a method to accurately characterize catalysts supported by mesoporous carbon will increase.…”
Section: Introductionmentioning
confidence: 99%